2021
DOI: 10.1038/s41598-021-86567-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical shape modeling of the talocrural joint using a hybrid multi-articulation joint approach

Abstract: Historically, conventional radiographs have been the primary tool to morphometrically evaluate the talocrural joint, which is comprised of the distal tibia, distal fibula, and proximal talus. More recently, high-resolution volumetric imaging, including computed tomography (CT), has enabled the generation of three-dimensional (3D) reconstructions of the talocrural joint. Weightbearing cone-beam CT (WBCT) technology provides additional benefit to assess 3D spatial relationships and joint congruency while the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 46 publications
3
35
1
Order By: Relevance
“…Figure13demonstrates the magnitude fields of shape deviations between our mean shape and the best talar shape found byTrovato et al (2017), and the mean shapes obtained byLiu et al (2020) andLenz et al (2021). The deviation fields indicated that the best talar shape presented by Trovato et al was more deviated from our predicted mean shape than the mean shapes predicted byLiu et al and …”
supporting
confidence: 49%
See 4 more Smart Citations
“…Figure13demonstrates the magnitude fields of shape deviations between our mean shape and the best talar shape found byTrovato et al (2017), and the mean shapes obtained byLiu et al (2020) andLenz et al (2021). The deviation fields indicated that the best talar shape presented by Trovato et al was more deviated from our predicted mean shape than the mean shapes predicted byLiu et al and …”
supporting
confidence: 49%
“…Shape deviations of the best talar shape presented by Trovato et al (2017), and the mean shapes obtained by Liu et al (2020) and Lenz et al (2021) from the mean shape predicted in this study [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations